Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1076/clin.17.2.235.16507
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Malingering: Supernormality

Abstract: Supernormality refers to the tendency to systematically deny the presence of common symptoms (e.g., intrusive thoughts). The current article describes the psychometric qualities of a 37-item self-report measure of supernormality (i.e., Supernormality Scale; SS). The SS was administered to nonclinical individuals (n=95), noncriminal psychiatric patients (n=28), nonpsychiatric delinquents (n=49), and a heterogeneous sample of forensic patients (n=59). Within the healthy control sample, some employees were instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 24 publications
1
47
2
4
Order By: Relevance
“…As mentioned before, previous priming studies have shown that when primes become too obvious, they no longer fly under the radar of explicit memory and might lose their power to affect subsequent behaviour (Bargh & Chartrand, 2000). There might, however, be an additional complication, which is that intense and explicit moral primes may perhaps encourage supernormality (Cima, Merckelbach, Hollnack, Butt, Kremer, Schellbach-Matties et al, 2003). Supernormality, or faking good, is another type of response bias that may distort brain-behaviour relationships.…”
Section: Figure 2 Roc Curves For Structured Inventory Of Malingered Smentioning
confidence: 99%
“…As mentioned before, previous priming studies have shown that when primes become too obvious, they no longer fly under the radar of explicit memory and might lose their power to affect subsequent behaviour (Bargh & Chartrand, 2000). There might, however, be an additional complication, which is that intense and explicit moral primes may perhaps encourage supernormality (Cima, Merckelbach, Hollnack, Butt, Kremer, Schellbach-Matties et al, 2003). Supernormality, or faking good, is another type of response bias that may distort brain-behaviour relationships.…”
Section: Figure 2 Roc Curves For Structured Inventory Of Malingered Smentioning
confidence: 99%
“…Perhaps then, participants exhibited a tendency to present themselves more favourably in the one-on-one situation in our laboratory than during the anonymous mass testing session. This tendency is coined supernormality by Cima, Merckelbach, Hollnack, Butt, Kremer, et al (2003). Our findings suggest that researchers using the DES are well-advised to reduce supernormality tendencies by stressing to participants that the data will be collected anonymously.…”
Section: Resultsmentioning
confidence: 85%
“…De SS-R is zodoende een instrument om 'faking good' oftewel supernormaliteit in kaart te brengen (Cima, 2003;Cima et al, 2003a;Cima, Van Bergen, & Cremer, ingediend voor publicatie). Bij 'faking good' ontkent de patie¨nt symptomen, die bij gezonde mensen wel voorkomen.…”
Section: Supernormality Scale-revised (Ss-r)unclassified
“…Dat is in deze groep van daders niet ongebruikelijk. Over het algemeen scoren patie¨nten in een forensische instelling beneden de afkapgrens van de SS-R (Cima et al, 2003a). Dat heeft ermee te maken dat deze patie¨nten vaak zo'n gezond mogelijke indruk willen maken, opdat ze de kliniek zo snel mogelijk kunnen verlaten.…”
Section: Discussie En Conclusieunclassified